Spatial variation of blood viscosity: Modelling using shear fields measured by a mu PIV based technique - Kaliviotis, Efstathios; Dusting, Jonathan; Balabani, Stavroula (My University, 2011)
The spatial characteristics of blood viscosity were investigated by combining a newly developed constitutive equation with shear deformation fields calculated from velocity measurements obtained by a μPIV based technique. Blood at physiological hematocrit levels and in the presence of aggregation was sheared in a narrow gap plate-plate geometry and the velocity and aggregation characteristics were determined from images captured using a high resolution camera. Changes in the microstructure of blood caused by aggregation were observed to affect the flow characteristics. At low shear rates, high aggregation and network formation caused the RBC motion to become essentially two-dimensional. The measured velocity fields were used to estimate the magnitude of shear which was subsequently used in conjunction with the new model to assess the spatial variation of viscosity across the flow domain. It was found that the non-uniform microstructural characteristics of blood influence its viscosity distribution accordingly. The viscosity of blood estimated in the core of the examined flow, using a zero-gradient core velocity profile assumption, was found to be significantly higher than the overall effective viscosity determined using other velocity profile assumptions.
Keywords: Aggregates; Micro-scale blood flow; RBC network formation